Análise matemática e estatística da produtividade de lavouras cafeeiras agroquímica e orgânica na região da alta paulista - Gabriel, José Eduardo de Ferreira [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Gabriel, Camila Pires Cremasco; Simon, Elias José [UNESP] (EIA Energy in Agriculture, 2011)
Studies with organic systems have shown the feasibility and ecological and social sustainability of these agroecosystems, unlike the systems agrochemicals (conventional) production. Some studies have concluded that for the model agrochemical exists less interaction between the flow of internal energy, basically the crop receives all inputs to production with no increase in "energy quality" within the system, while in the organic model of production has increased interaction between different resources in the system. The current economic and ecological crisis, exposed no sustainability of the production pattern of industrialized agriculture developed in a way, showing the dependence of developed countries on imports of agricultural commodities produced in the third world, among there coffee. Given these facts, developed a survey to identify problems in the Alta Paulista region, west of São Paulo State, in relation to coffee production systems. Actually, the fundamental problem, according to the research, farmers in this region, is to choose a viable production system correctly (environmental, social and economic); agrochemical or organic. The objectives of this study were to analyze the yield of production systems and agro-chemical and organic coffee in the period from 2003 to 2007, in 30 producing properties, located in this region, in order to point the production system to produce the highest yield. According to the methodology of CONAB, data collected were recorded on spreadsheets to be used as variables in statistical analysis models and mathematics. We performed a descriptive analysis of productivity data and were used for statistical analysis tests for parametric and nonparametric analysis of variance. The mathematical analyses of the curves were prepared with Origin for Windows 6.0 software, which uses numerical methods to fit the data supplied to a function of variable parameters. Unlike conventional systems of production, the organic system showed greater viability of the production model. Furthermore, with the quantitative modeling proposal, it is possible to perform the evaluation of these types of investments, providing more security to the farmer at the time of decision.

Estudos realizados com sistemas orgânicos têm mostrado a viabilidade e sustentabilidade ecológica e social desses agroecossistemas, ao contrário dos sistemas agroquímicos (convencionais) de produção. Alguns estudos concluíram que o modelo agroquímico existe pouca interação entre os fluxos de energia interna, basicamente a lavoura recebe todos os insumos para a produção não havendo aumento na ?qualidade energética? interna ao sistema, enquanto que no modelo orgânico de produção apresenta maior interação entre os diferentes recursos existentes no sistema. As atuais crises econômica e ecológica, expõem a insustentabilidade do padrão produtivo da agricultura desenvolvida de forma industrializada, evidenciando à dependência dos países do primeiro mundo na importação de commodities agrícolas produzidas no terceiro mundo, dentre elas, o café. Diante destes fatos desenvolveu-se uma pesquisa para identificar os problemas na região da Alta Paulista, Oeste do Estado de São Paulo, com relação aos sistemas de produção de café. Atualmente, o problema fundamental, de acordo com a pesquisa realizada, dos agricultores nesta região, reside na escolha de um sistema de produção corretamente viável (ambiental, social e econômico); agroquímico ou orgânico. Os objetivos deste estudo foram analisar a produtividade dos sistemas de produção de café orgânico e agroquímico e no período de 2003 a 2007, em 30 propriedades produtoras, localizadas nesta região, com a finalidade de apontar o sistema de produção que apresente a maior produtividade. De acordo com a metodologia da CONAB, os dados coletados foram registrados em planilhas eletrônicas para serem utilizados como variáveis nos modelos de análises estatística e matemática. Realizou-se uma análise descritiva dos dados de produtividade e utilizou-se para análise estatística o testes paramétricos e não paramétricos para análise de variância.
Mathematics and statistical analysis of productivity of agrochemicals and organic coffee plantations in alta paulista region
Keywords: Agroecosystems; Quantitative modeling; Statistical analysis and mathematical; Agroecossistemas; Modelagem quantitativa; Análises estatísticas e matemática